2023
DOI: 10.3390/ijms24065576
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite or Fluorapatite—Which Bioceramic Is Better as a Base for the Production of Bone Scaffold?—A Comprehensive Comparative Study

Abstract: Hydroxyapatite (HAP) is the most common calcium phosphate ceramic that is used in biomedical applications, e.g., as an inorganic component of bone scaffolds. Nevertheless, fluorapatite (FAP) has gained great attention in the area of bone tissue engineering in recent times. The aim of this study was a comprehensive comparative evaluation of the biomedical potential of fabricated HAP- and FAP-based bone scaffolds, to assess which bioceramic is better for regenerative medicine applications. It was demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Contact with HAP or FAP did not evoke a significant neutrophil response. A previous report indicated that HAP and FAP did not generate a serious pro-inflammatory response from immune cells in vitro [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Contact with HAP or FAP did not evoke a significant neutrophil response. A previous report indicated that HAP and FAP did not generate a serious pro-inflammatory response from immune cells in vitro [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, biomaterials were made of a polymeric chitosan–agarose phase (both biopolymers were purchased from Sigma-Aldrich Chemicals, Warsaw, Poland) and mineral phase in the form of either hydroxyapatite nanopowder (Sigma-Aldrich Chemicals, Warsaw, Poland) or fluoroapatite nanopowder. Fluoroapatite was produced according to the procedure described previously [ 4 ]. The mixture of 2% ( w / v ) chitosan (50–190 kDa molecular weight), 5% ( w / v ) agarose (gel point 36 ± 1.5 °C) and 40% ( w / v ) bioceramics (HA or FA nanopowder) were prepared in 2% ( v / v ) acetic acid solution (Avantor Performance Materials, Gliwice, Poland).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations